Applied physiology of water polo - Smith, H. K. (Sports Medicine, 1998)
Water polo has been played for over a century. While the rules of the game have evolved considerably over this time, the sport has consistently remained, physiologically, a highly demanding activity. Much attention has been paid to the technical and strategic elements of the game; however, despite the potential for improvements in athletic performance and the maintenance of athletes' health, there are few published studies (particularly in English) on the physical and physiological demands and adaptations to water polo training and competition. Game analyses have demonstrated that water polo is an 'intermittent' sport comprised of intense bursts of activity of <15 seconds duration with intervening, lower intensity intervals averaging <20 seconds duration. Physiological measurements obtained during game play indicate a cumulative effect of the repeated sequences of activities and suggest there is a high metabolic demand on the athletes. The multiple individual skills and movements required for playing water polo also place considerable demands on the neuromuscular system. Observations of the frequency and duration of the different activities, and of the physiological responses to participating in a water polo match, are initial sources of information for designing training programmes specific to the game and to the different playing positions. The physical and physiological attributes of elite water polo players offer some insight into the minimum requirements for participation and the adaptations that result from training and competition. Further systematic documentation and experimentation are required to facilitate the design and specification of individual training programmes and to better understand the long term effects of water polo on athletes' health.